2015
DOI: 10.1038/srep13252
|View full text |Cite
|
Sign up to set email alerts
|

Virulence from vesicles: Novel mechanisms of host cell injury by Escherichia coli O104:H4 outbreak strain

Abstract: The highly virulent Escherichia coli O104:H4 that caused the large 2011 outbreak of diarrhoea and haemolytic uraemic syndrome secretes blended virulence factors of enterohaemorrhagic and enteroaggregative E. coli, but their secretion pathways are unknown. We demonstrate that the outbreak strain releases a cocktail of virulence factors via outer membrane vesicles (OMVs) shed during growth. The OMVs contain Shiga toxin (Stx) 2a, the major virulence factor of the strain, Shigella enterotoxin 1, H4 flagellin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(159 citation statements)
references
References 59 publications
6
152
0
Order By: Relevance
“…Alternatively, the presence of higher numbers of cytosolic proteins in O104:H4 could result from outer membrane vesicles (OMVs). Recently, Kunsmann and colleagues showed that O104:H4 shed OMVs containing significant amounts of Shiga toxin in addition to other virulence factors and cytosolic proteins that bind to and are internalized by human intestinal epithelial cells (48). The large amount of Shiga toxin 2B we observed supports this hypothesis, but we have yet to show that OMVs can explain the large number of cystosolic proteins we observed in O104:H4 growth medium.…”
Section: Discussionsupporting
confidence: 51%
“…Alternatively, the presence of higher numbers of cytosolic proteins in O104:H4 could result from outer membrane vesicles (OMVs). Recently, Kunsmann and colleagues showed that O104:H4 shed OMVs containing significant amounts of Shiga toxin in addition to other virulence factors and cytosolic proteins that bind to and are internalized by human intestinal epithelial cells (48). The large amount of Shiga toxin 2B we observed supports this hypothesis, but we have yet to show that OMVs can explain the large number of cystosolic proteins we observed in O104:H4 growth medium.…”
Section: Discussionsupporting
confidence: 51%
“…The capability of gram-negative bacteria to release lipid vesicles has been recently reported for EHEC-derived hemolysin, which is delivered to the intestine in a free and a vesicular form ( 102 ). However, Stxs entrapped in outer membrane vesicles and binding as well as internalization of toxinloaded vesicles by human intestinal epithelial cells suggest a novel mechanism to deliver pathogenic cargoes and injure host cells ( 101 ). Thus, these novel fi ndings on extracellular transport of AB 5 toxins in lipid vesicles nicely show an unexpected analogy when compared with the intracellular vesicular transportation and retro-translocation of GSL-bound toxins through the Golgi apparatus and the endoplasmic reticulum ( 35 ).…”
Section: Statistics Of Lipid Distribution In Drm and Nondrm Fractionsmentioning
confidence: 99%
“…Although the initial mechanisms of GSL-toxin interaction are now partly understood, much less is known about the release of toxins from pathogenic enterobacteriaceae into the gut and their interaction with intestinal epithelial cells. Evidence has increased, for example, for V. cholerae toxin and the Stx of the E. coli O104:H4 outbreak strain, that released toxins are associated with outer membrane vesicles, which are shed by gram-negative bacteria during growth ( 100,101 ). The capability of gram-negative bacteria to release lipid vesicles has been recently reported for EHEC-derived hemolysin, which is delivered to the intestine in a free and a vesicular form ( 102 ).…”
Section: Statistics Of Lipid Distribution In Drm and Nondrm Fractionsmentioning
confidence: 99%
“…Secreted effector proteins are of particular interest as they are frequently required for full virulence [7]. Additionally, some bacterial pathogens such as certain Shigella dysenteriae or Escherichia Coli strains express Shiga toxins generally during their lytic cycle [8] or release these toxins through Outer Membrane Vesicles during their growth phase [9], leading to the inhibition of protein synthesis or activation of the apoptotic pathways of their host cells. As the number of bacterial host-pathogen interaction studies increases, they demonstrate that while bacteria generally do not rely on host cell machinery for the purpose of replication as directly as viruses do, they do seem to disrupt the immune response [10] and interact preferentially with the hosts’ cytoskeleton as a mean of motility, invasion of the host tissues [11] and escape of phagocytic cells [12].…”
Section: Introduction To Host-pathogen Protein-protein Interactionsmentioning
confidence: 99%